Effectiveness of Resin-Infiltration in Masking White Spot Lesions and Enamel Defects, Color Stability and Inhibition of Caries Progression: A Systematic Review - Sravya, Amaradri; Vinay, Chandrappa; Uloopi, Kadidal; Ravigna, Peddi; Chaitanya, Penmatsa; Cheeli, Spandana (UI Scholars Hub, 2025)
Objective: The study aims to demonstrate the efficacy of resin-infiltration in masking white spot lesions and enamel defects, color stability, and caries progression inhibition in primary and permanent teeth. Methods: PubMed, Cochrane library, Wiley Online Library, and Google Scholar databases were searched from 2018 to 2022 and only randomized controlled clinical trials (RCT’s) were included. The studies were analyzed regarding the clinical efficacy of resin-infiltration in masking white spot lesions and enamel defects, color stability, and inhibition of caries progression. Results: Of the 14 articles identified, 5 RCTs were included. The quality of the studies was assessed to be high concerning allocation and outcomes. All the included studies showed significant differences in caries progression, masking, and color stability between test and control groups. Conclusion: The use of resin filtration significantly improved clinical outcomes in controlling proximal caries lesions and masking and color stability of enamel defects on smooth surfaces, compared to other non-invasive approaches.